1999
DOI: 10.1161/01.str.30.10.2101
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Coagulation and Fibrinolysis Markers in Acute Ischemic Stroke Treated With Recombinant Tissue Plasminogen Activator

Abstract: Background and Purpose-Shifts of the balance between coagulation and fibrinolysis play a crucial role in pathogenesis and treatment of cerebral ischemia. In this study, we characterized the kinetics of hemostatic abnormalities induced by acute ischemic stroke and its thrombolytic (recombinant tissue plasminogen activator [rtPA]) or anticoagulant (heparin) treatment. Methods-Systemic generation of molecular markers of hemostasis (fibrin monomer, D-dimer, thrombin-antithrombin complex, and fibrinopeptide 1.2) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 22 publications
4
53
0
2
Order By: Relevance
“…Indeed, we observed a modest increase of D-dimer antigen, an indicator of the formation of factor XIIIa cross-linked fibrin. Fassbender et al 8 reported that fibrin monomers and D-dimer antigen were substantially elevated for 72 hours after standard thrombolytic therapy in stroke patients. Similar findings were reported for thrombolysis in myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed a modest increase of D-dimer antigen, an indicator of the formation of factor XIIIa cross-linked fibrin. Fassbender et al 8 reported that fibrin monomers and D-dimer antigen were substantially elevated for 72 hours after standard thrombolytic therapy in stroke patients. Similar findings were reported for thrombolysis in myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…5,19 From experimental data obtained in a rat thromboembolic stroke model, simultaneous treatment with thrombolytic and GPIIb/IIIa inhibitory agents significantly attenuates neuronal damage with no increase in the incidence of cerebral hemorrhage. 9,10 Compared with full-dosage rtPA, an enhancement in large-and small-vessel patency contributed to smaller infarct sizes and a better neurological outcome.…”
Section: Recanalization and Lesion Size After Combined Thrombolysismentioning
confidence: 99%
“…4 As in myocardial infarction, treatment of acute ischemic stroke with thrombolytic agents such as rtPA inevitably leads to concomitant activation of the coagulatory system. 5 Thus, even in successful initial recanalization, neurological deterioration related to repeated vessel occlusions is observed in every third case after rtPA treatment. 6 Combined thrombolytic treatment with fibrinolytic and platelet glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitory agents led to improved patency rates in myocardial reperfusion therapy compared with rtPA alone.…”
mentioning
confidence: 99%
“…10,11 Reocclusion after tPA treatment is induced, at least in part, by the activation of the coagulation cascade by tPA. 12,13 These findings indicate that the use of antiplatelet drugs is potentially a double-edged sword in the context of tPA treatment; that is, use of antiplatelet agents is likely to be beneficial for stroke outcome despite increased risk of hemorrhagic infarction. Consistent with these findings, a randomized controlled trial in the Netherlands has shown that thrombolysis in combination with antiplatelet drugs prevented reocclusion and improved the clinical outcome.…”
mentioning
confidence: 99%